CD68 in Cerebral Aneurysms of Smokers and Nonsmokers: An Immunohistochemical Analysis - Crusius, Cassiano Ughini; Cambruzzi, Eduardo; Crusius, Marcelo Ughini; Aguiar, Paulo Henrique Pires de; Tognon, Alexandre Pereira; Crusius, Paulo Sérgio; Stefani, Marco Antônio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background There is some evidence indicating that inflammation of the aneurysmal wall is related to aneurysmal growth and rupture. The presence of CD68 may indicate greater inflammatory activity. The objective of this study is to evaluate CD68 immunoexpression in surgically resected brain aneurysms and its association with smoking.Methods The resected brain aneurysmal walls after microsurgical clipping were envoyed to immunohistochemistry investigation. The objective was to evaluate the expression of CD68 and CD34 antibodies. The associations between inflammatory markers, smoking, and rupture were tested using Fischer's exact test.Results CD68 immunoexpression in the tunica media was associated with larger aneurysms: 7.0 mm (7.0–9.0 mm) versus 5.0 mm (3.5–5 mm; p = 0.011). There was no statistically significant association between smoking and CD68 expression in the tunica media (p = 0.234) or in either the tunica media or the tunica intima (p = 0.628). There was also no statistically significant association between hemorrhagic presentation of the aneurysm and CD68 expression in the tunica media (p = 0.689) or in either the tunica media or the tunica intima (p = 0.348). Therefore, the presence of CD68-positive cells in the aneurysmal walls indicates an association with size, especially if the tunica media is exclusively compromised (p = 0.011).Conclusion Immunohistochemistry investigation for CD68 antibodies was used to determine histiocytic infiltration. Adequately powered studies are necessary to further investigate the association between CD68-positive cells and both smoking history and hemorrhagic presentation of aneurysms.
Keywords: CD68; brain aneurysms; smokers